Parenting style, family support, and relapse among schizophrenia patients: a literature review - AV Sri Suhardiningsih; Dya Sustrami; Mundakir Mundakir (PAGEPress Publications, 2024)
Schizophrenia is a mental health problem that is quite widespread in Indonesia. Relapse among patients with Schizophrenia is related to parenting style and family support. This study aimed to present a literature review that address parenting style, family support, and relapse among schizophrenia patients. Three databases were used in this study, ProQuest, Google Scholar, and PubMed. The keywords were used according to the Medical Subject heading (Mesh): Parenting and families support or emotional support and family functioning and relapse and Schizophrenia. We limited the articles from 2020-2022 and in English. We obtained 434 articles which divided into Google Scholar 214 articles, ProQuest 134 articles, and PubMed 86 articles. In the end, we obtained six articles. The methodology of articles was evaluated using JBI Critical checklist. Scores less than 50% were excluded from the study to ensure the quality of the articles. The review results showed that parenting style and family support are risk factors contributing to relapse among schizophrenia patients. However, there was one article showed that there was no correlation between family cohesion and relapse among schizophrenia patients. Parenting style and family support has a function in preventing relapse among schizophrenia patients. So, parenting style and family support management are needed to address intervention for preventing relapse among schizophrenia patients.